Assessing concrete carbonation resistance through air permeability measurements. (1st May 2015) - Neves, R.; da Fonseca, B. Sena; Branco, F.; de Brito, J.; Castela, A.; Montemor, M.F.
Highlights: Derivation of a theoretical relationship between permeability and carbonation rate. Validation of theoretical relationship with experimental results. Relationship between air permeability and carbonation rate depends on cement type. Proposal of a relationship between air permeability and carbonation rate. Indirect assessment of carbonation resistance through air permeability is advised. Abstract: Performance-based design and specification of concrete for durability is the most efficient way to achieve the intended service life; its use has been increasing. However, to have a consistent approach, the durability related properties must be assessed onsite. This assessment can provide useful and realistic information to estimate the service life of newly built concrete structures. Thus, this work aims at evaluating the suitability of a non-destructive onsite test method to provide such information. A preliminary study, comprising tests on air permeability and carbonation resistance of several concrete mixes and an analysis of its results, was carried out. The analysis allowed proposing an analytical model, based on the calibration of a theoretical model, correlating air permeability with resistance to carbonation. This allows estimating reliably carbonation resistance through air permeability results. Although further research is needed, to provide more data, the results encourage the use of a simple test method that operates on a completely non-destructive basis. Thus, a contribution to a more consistent approach towards the achievement of durable concrete structures and of the associated positive environmental impacts is provided.